2019
DOI: 10.1021/acsomega.9b01285
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3-Triazolium-Derived Mesoionic Carbene Ligands Bearing Chiral Sulfur-Based Moieties: Synthesis, Catalytic Properties, and Their Role in Chirality Transfer

Abstract: 1,2,3-Triazole-derived mesoionic carbenes (MICs) having a chiral sulfur functional group at the C5 position are easily available through a CuAAC between chiral alkynyl sulfoxides and different azides. The MICs form complexes with several metals (Au, Ag, Ir, Rh, and Ru) that are enantiomerically pure. Moreover, enantiomerically pure MIC sulfinilimines are obtained from the corresponding sulfoxide retaining the chirality. Through this article, the participation of sulfoxide moieties in different catalytic and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…17 We were interested in determining the suitability as catalysts of the above prepared β-lactam and penicillin substituted MIC-complexes. Based on our previous experience using MIC metal complexes as catalysts 18 we chose the Au( i ) cycloisomerization of enynes and the Pt( ii ) hydrosilylation of alkynes to determine both the catalytic activity of these complexes and the integrity of the labile β-lactam (especially the penicillin bicyclic ring) during the catalytic process. This fact could be tested by determining the influence of the substitution on the four membered ring in the catalytic outcome.…”
Section: Resultsmentioning
confidence: 99%
“…17 We were interested in determining the suitability as catalysts of the above prepared β-lactam and penicillin substituted MIC-complexes. Based on our previous experience using MIC metal complexes as catalysts 18 we chose the Au( i ) cycloisomerization of enynes and the Pt( ii ) hydrosilylation of alkynes to determine both the catalytic activity of these complexes and the integrity of the labile β-lactam (especially the penicillin bicyclic ring) during the catalytic process. This fact could be tested by determining the influence of the substitution on the four membered ring in the catalytic outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Three differently substituted 1,2,3‐triazolyl sulfoxides 3 were obtained by reaction of NfN 3 (nonafluorobutanesulfonyl or nonaflyl azide) and the corresponding aniline to generate “in situ” the azide, [ 17 ] and subsequent Cu‐catalyzed azide‐alkyne cycloaddition in mixtures MeOH/H 2 O/Et 2 O as solvent, using CuSO 4 · 5H 2 O/sodium ascorbate as the catalyst. [ 8 ] The yields on compounds 3 were acceptable to good (41–80 %) (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…During our work in the synthesis of transition metal complexes having 1,2,3-triazolylidene (MIC) ligands with enantiopure sulfoxide and sulfoxiimine moieties, [8] we have reported the role of the chiral mesoionic carbene ligand (MIC) in defining the catalytic reactivity of their Au(I) derivatives, [9] preparing enantiopure chiral-at-metal complexes, [10] and enantiopure complexes having chiral-at-metal and chiral planar metallocene moieties. [11] On the other hand, our work in push-pull systems containing a Cr(0) and W(0) Fischer metal carbene moiety, I, clearly demonstrated that the system geometry is reflected in the deactivation of the fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoionic carbenes (MICs) have recently attracted a lot of attention in the field of transition-metal catalysis for organic transformations [1][2][3][4][5][6][7][8][9] and photophysical materials. [10][11][12][13][14][15][16] In particular, 1,2,3-triazol-5-ylidene (triazolylidene) is the most attractive ligand motif and has been well established because it can be easily synthesized via the [3 + 2] Huisgen reaction between alkynes and azides.…”
Section: Introductionmentioning
confidence: 99%